SPECIAL DIVERSITY OF THE RURAL AREAS REGARDING THEIR INFRASTRUCTURAL OUTFIT - Kropsz, Irena (Acta Scientiarum Polonorum. Oeconomia, 2002)
The rural areas in Poland are very diverse. There are those wealthier ones, more advanced in the process of its transformation and, on the other hand there are some poor regions which remain significantly underdeveloped. Even within one voivodship a lot of differences can be observed and moreover, there are many differences even among one community. This paper discusses the level of equipment of basic technical, social and economic elements in the chosen communities in Lower Silesia region. The statistical method of point valorization was used in the analyse in order to highlight differences among communities and among villages within one community.